2013
DOI: 10.1017/s0007485313000564
|View full text |Cite
|
Sign up to set email alerts
|

Ants affect the infestation levels but not the parasitism of honeydew and non-honeydew producing pests in citrus

Abstract: Abstract:22 Ants can act simultaneously as predators and as hemipteran mutualists, and thus may affect 23 the composition and the population dynamics of a wide arthropod community. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 68 publications
(139 reference statements)
4
34
1
2
Order By: Relevance
“…Apparently, ant presence is associated with increased abundances of P. pergandii, as already found for other armored scales (Calabuig et al, 2013;Pekas et al, 2010;Yoo et al, 2013). Other parasitoid species of non-honeydew producers did not follow this trend.…”
Section: It Was Surprising To See That Encarsia Inquirenda Silvestri supporting
confidence: 66%
See 3 more Smart Citations
“…Apparently, ant presence is associated with increased abundances of P. pergandii, as already found for other armored scales (Calabuig et al, 2013;Pekas et al, 2010;Yoo et al, 2013). Other parasitoid species of non-honeydew producers did not follow this trend.…”
Section: It Was Surprising To See That Encarsia Inquirenda Silvestri supporting
confidence: 66%
“…In fact, the impact of the three species on the community structure of natural enemies was quite similar. In a previous study it was found that the three ant species induced similar increases of the herbivore populations A. aurantii and A. floccossus (Calabuig et al, 2013). …”
Section: Species Richness Diversity and Community Structure Of Predamentioning
confidence: 79%
See 2 more Smart Citations
“…The ant attendance symbiosis provides protection from natural enemies, results in higher aphid growth rates, improves hygiene conditions and increases the transport and dispersal abilities of the pest, thus increasing the rate of infestations (Buckley, 1987;Stadler and Dixon, 2005;Calabuig et al, 2014). This myrmecophilous association was described specifically for A. spiraecola on citrus (Shindo, 1972;Pekas et al, 2011;Tena et al, 2013) (Figure 4).…”
Section: Ecologymentioning
confidence: 90%